1996
DOI: 10.1111/j.1600-0714.1996.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral minor salivary gland tumors: a retrospective study of 62 cases in a Venezuelan population

Abstract: From 1968 to 1992 sixty-two cases of tumors of minor salivary glands were diagnosed from a Venezuelan population at the Oral Histopathology Laboratory of the Central University of Venezuela School of Dentistry. The diagnosis of individual tumors was based on the 1991 World Health Organization classification. Tumors were analyzed considering histological type, age and sex of the patient, and intraoral location. Pleomorphic adenomas constituted the most common histological diagnosis of the benign sample (71%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
58
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 11 publications
22
58
3
Order By: Relevance
“…Intraoral MSGTs accounted for 0.28-1.9% of the specimens, as reported by other authors in USA, Japan, Venezuela and Thailand. 4, [9][10][11] In our series, malignant neoplasms constituted 46.3% of the cases which is in agreement with the results of the most previous studies. 5,9,12 However, some have shown a predominance of malignant tumors.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Intraoral MSGTs accounted for 0.28-1.9% of the specimens, as reported by other authors in USA, Japan, Venezuela and Thailand. 4, [9][10][11] In our series, malignant neoplasms constituted 46.3% of the cases which is in agreement with the results of the most previous studies. 5,9,12 However, some have shown a predominance of malignant tumors.…”
Section: Discussionsupporting
confidence: 82%
“…2-6,9-11,14,16 Figure 2 is similar to some reports, 14,15,17 but the authors in USA, Brazil, Venezuela, Australia, China and Ansari on 18 cases of MSGTs in central Iran, reported that MEC was the most frequent. 6,10,16,[18][19][20][21] According to these data, there is a geographic variation in relative frequency of Ad CC versus MEC. However, these two neoplasms are the first and second malignant tumors in the most series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to other publications 12 , although they are different from studies reporting the mucoepidermoid carcinoma as the most frequent malignant neoplasia 2,14 . However, in the present study, two cases represent the difference between the number of cystic adenoid carcinoma and of mucoepidermoid, which is not considered significant when compared to other series.…”
supporting
confidence: 67%
“…Concerning head and neck regions, it is known that tumors of the salivary glands correspond, on average, to 3% of the affections on this site, the majority being of epithelial origin 1,2 . They present varied etiology and several risk factors have been identified so far, although lack of information from medical records and clinical files minimize the importance of these tumors in the tumorigenesis of salivary glands 3 .…”
Section: Introductionmentioning
confidence: 99%